2019
DOI: 10.1111/andr.12728
|View full text |Cite
|
Sign up to set email alerts
|

Low serum testosterone levels and the incidence of chronic kidney disease among male adults: A prospective population‐based study

Abstract: Background: Despite existing evidence regarding the role of testosterone as a protective factor for the kidney function in male adults, there are conflicting and inconclusive results on the influence of testosterone deficiency on developing chronic kidney disease (CKD).Objective: This study aimed to investigate the incidence and hazard ratio of CKD among male adults with low testosterone levels compared to controls with normal testosterone levels. Materials and Methods: During a 15-year follow-up study, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…It has been reported that TT has beneficial effects on kidney functions and that renal functions are also associated with erectile complaints. Especially in CKD patients, low TT levels have been associated with the progression of CKD [22]. In this study plan, we tried to examine whether ED is an early marker in patients who have ED complaints and have not had a problem or diagnosis associated with CKD before.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TT has beneficial effects on kidney functions and that renal functions are also associated with erectile complaints. Especially in CKD patients, low TT levels have been associated with the progression of CKD [22]. In this study plan, we tried to examine whether ED is an early marker in patients who have ED complaints and have not had a problem or diagnosis associated with CKD before.…”
Section: Discussionmentioning
confidence: 99%
“…29 On the other hand, the study by Amiri et al revealed that a hypogonadal state increased the hazard ratio of developing CKD in males by 1.26 in comparison to eugonadal men. 30 Aside from the influence of testosterone levels on muscle mass, this anabolic hormone can also affect fat tissue. Some researchers noted an inverse correlation between testosterone concentrations and fat mass in individuals with normal kidney function as well as in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In CKD, sexual dysfunction is common in men [129]. Lower testosterone levels have a deleterious role since they are associated with an increased risk of developing CKD [130] and mortality in male patients receiving dialysis [131]. Shoskes et al reported a higher risk of graft loss in male kidney transplant recipients with lower testosterone levels [132].…”
Section: Influence Of Sex Hormones In the Kidneymentioning
confidence: 99%